Health insurance trends from 2004 to 2022: a bibliometric analysis - Damayanti, Fitriani Nur; Santosa, Budi; Suparman, Suparman; Kusumawati, Erna; Istiana, Siti (Faculty of Medicine, Universitas Trisakti, 2024)
The goal of health systems implemented at international, national, or regional level is to improve health effectively and efficiently by all available means, including community efforts, special education, military, and government, thereby improving public health at all levels. Health issues as national issues need top priority. Inequalities in mortality risk are inseparable from issues surrounding the health policy debate. Public health level is assessed through several indicators. Health Policy in law regulates the right to health. Proposed health system goals at international, national, or regional levels are usually not measured by human rights standards and instruments. Universal Health Insurance is expected to provide benefits. Health services are provided as medicines and treatments. This review aimed to determine trends in number of publications and visualize linkages of health insurance topics through bibliometric analysis. This was a systematic review with steps following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) diagram using 661 scientific articles published between 2004 and 2022, followed by inclusion and exclusion criteria from Dimensions database. Review of articles was by means of Vosviewer app. Our study results contributed to research roadmap development on health insurance. The limitation is that app.dimension.ai and google scholar databases are periodically updated, such that bibliometric analysis of health insurance should be repeated in the near future. Because this bibliometric analysis only extracted scientific article data from app.dimension.ai database, further research should add another database for broader and more comprehensive understanding of health insurance.